Hebrew Nominal Patterns in the Speaker’s Mind - Shatil, Nimrod (Hebrew studies, 2016)
Some psycholinguists have claimed that the seven verbal Hebrew patterns are part of the mental lexicon (alongside the lexemes and the roots) whereas the nominal patterns are not. The difference is explained by the great number (over 100) of the nominal patterns and their semantic inconsistency. This claim is questioned by the present article. The number of the living or productive nominal patterns system is around thirty. Thirteen of them are common to the verbal and the nominal systems (five regular noun actions, five active participles, three perfective participles), and they are as frequent as the verbal forms themselves. The living nominal pattern system acts similarly to that of the verbal patterns. This is demonstrated by three phenomena that display the speakers’ awareness of the nominal patterns’ functions: a) pattern switching when there is no matching between the pattern and the content of the word; b) colloquial derivation in the living patterns; c) acceptance or rejection of proposed new items according to the extent of their adaptation to the pattern’s function. The evidence is naturalistic data taken from the speakers’ linguistic behavior as manifested in spoken and written sources including the Internet and television shows.